SOCIAL RELATIONSHIPS IN CONGREGATIONAL PRAYERS TOWARD SOCIAL LIFE IN MAKASSAR CITY DURING COVID-19 PANDEMIC - Sumardin, Andi; Sultan, Lomba; Said, Nurman; Ridwan, M Saleh (Jurnal Diskursus Islam, 2021)
This paper elaborates the social relationships in congregational prayers toward the social life in Makassar City during Covid 19 pandemic. The study used qualitative method and took place in Makassar City, South Sulawesi Province. The researchers applied phenomenological, normative, and anthropological approaches and used in-depth interviews, non-participatory observation, and documentation for data collection. The research instrument was interview guide and observation guide. After the data was collected, it was analyzed through three stages; data reduction, data presentation, and data verification/ conclusions drawing. The data triangulation involved credibility, dependability, confirmability, and transparency criteria. The results show that the role of congregational prayers on social problems in Makassar city during the Covid-19 pandemic is to educate the public directly to face the pandemic, encourage more self-reflection in interpreting the pandemic, and take wisdom from the situation.